Legal personality of Takaful fund: myth or reality? - Salleh, Safinar; Ibrahim, Uzaimah; Zahraa, Mahdi (2015)
Ideally, takaful should be formed on mutual basis and operated by a mutual company owned by takaful participants. Under the mutual structure, the company has its own legal personality whereby it can own assets and carry liabilities. At present, takaful is widely formed under a hybrid of mutual and commercial structure operated by licensed takaful companies. Under this hybrid structure, a takaful fund shall be established on mutual basis and owned by the participants. On the other hand, the takaful company is a commercial entity proprietarily owned by shareholders. Several issues arising in the operation of takaful under this hybrid structure, such as the status of ownership of takaful fund and its surplus. The fund neither belong to the takaful company nor the participants because they have donated their contributions. Some scholars say, the fund itself is the owner of all the contributions, profits and surplus. To enable the fund to become the owner of the contributions and the surplus, it is suggested that the fund should have its own legal personality. Thus, this paper aims to determine the need and feasibility of assigning a legal personality to the takaful fund from Shariah and legal perspectives. It discusses the concept of legal personality in Islamic law followed by the analysis on its applicability to the takaful fund. This study is an academic legal research which involves doctrinal analysis and review of relevant statutes and literatures including Islamic classical texts and scholarly journals and publications. In principle, this study finds that there is a need to assign legal personality to the takaful fund in order to solve certain Shariah issues in the operation of takaful. From the legal perspective, IFSA seems to recognise the legal personality of takaful fund.